Manipulation and reduction of paediatric fractures of the distal radius and forearm using intranasal diamorphine and 50% oxygen and nitrous oxide in the emergency department - Kurien, Thomas; Price, K.R.; Pearson, Richard G.; Hunter, J.B. (British Editorial Society of Bone and Joint Surgery, 2016)
A retrospective study was performed in 100 children aged between two and 16 years, with a dorsally angulated stable fracture of the distal radius or forearm, who were treated with manipulation in the emergency department (ED) using intranasal diamorphine and 50% oxygen and nitrous oxide. Pre- and post-manipulation radiographs, the final radiographs and the clinical notes were reviewed. A successful reduction was achieved in 90 fractures (90%) and only three children (3%) required remanipulation and Kirschner wire fixation or internal fixation. The use of Entonox and intranasal diamorphine is safe and effective for the closed reduction of a stable paediatric fracture of the distal radius and forearm in the ED. By facilitating discharge on the same day, there is a substantial cost benefit to families and the NHS and we recommend this method.